2021
DOI: 10.21608/ejabf.2021.160288
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal, biological, and histopathological alterations induced by pomegranate peel extract, Punica granatum against Culex pipiens L. (Diptera: Culicidae)

Abstract: Dipterous insects cause serious public health problems for both humans and animals (Linthicum, 2012). In Egypt, Culex pipiens (Diptera: Culicidae), has been investigated and declared as a vector of several diseases (El-Zayyat et al., 2017). It transmits Rift valley fever virus (Dodson et al., 2017), Japanese encephalitis (Chancey et al., 2015), Wuchereria bancrofti accredited for human lymphatic filariasis transmission (Joseph et al., 2011), and West Nile virus (Bassal et al., 2017). Culex pipiens was incrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…All tested extracts showed a significant reduction in protein, lipids, and carbohydrate contents of treated larvae compared to untreated larvae, which may impair the survival and development of the larvae. Our results were in accordance with previous reports that reported that larvicides have a deleterious impact on larval growth and development, causing alterations in their metabolic and biochemical processes [ 62 ].…”
Section: Resultssupporting
confidence: 93%
“…All tested extracts showed a significant reduction in protein, lipids, and carbohydrate contents of treated larvae compared to untreated larvae, which may impair the survival and development of the larvae. Our results were in accordance with previous reports that reported that larvicides have a deleterious impact on larval growth and development, causing alterations in their metabolic and biochemical processes [ 62 ].…”
Section: Resultssupporting
confidence: 93%
“…Previous studies reported that the ethanol extract of pomegranate fruits exhibited larvicidal activity against C. pipiens 17 . In addition, larvicidal activity against C. pipiens was reported for the acetone and petroleum ether extracts of pomegranate peels 44,45 . Interestingly, the methanol extract of pomegranate rind exhibited the highest toxicity on the fourth instar larvae of Culex quinquefasciatus and Cricotopus gelidus when compared to other extracts (hexane and ethyl acetate) 46 .…”
Section: Resultsmentioning
confidence: 89%
“…42 In this regard, the metabolic profiles of seven petroleum ether extracts of pomegranate peels. 44,45 Interestingly, the methanol extract of pomegranate rind exhibited the highest toxicity on the fourth instar larvae of Culex quinquefasciatus and Cricotopus gelidus when compared to other extracts (hexane and ethyl acetate). 46 Therefore, in this study several concentrations of the peel methanol extracts of seven pomegranate cultivars were evaluated against newly molted third instar C. pipiens larvae and their larvicidal effects were determined.…”
Section: A Comparative Untargeted Metabolomic Study Using Multivariat...mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, in treated larvae of Tuta absoluta with phenthoate, imidacloprid, and dinotefuran, Radwan and Taha [48] found a correlation between the loss of various proteins and the reduction of band intensity when using SDS PAGE. In addition, Farag et al [49] observed the disappearance of normal protein bands in the treated Cx. pipiens larvae with pomegranate peel extracts.…”
Section: Discussionmentioning
confidence: 94%